(untitled) (International Journal of Engineering and Computer Science, 2016)
Radar (Radio Detection And Ranging) is an object – detection system that uses radio waves to determine the range, angle or Velocity of objects. It can be used to detect aircraft, ships, guide missiles, motor vehicles, weather formations and terrain. In addition, the radar system can also guide the missile towards the hostile target which is called the GUIDANCE RADAR. In this radar, the hostile target continuously tracked with the minimum error variance and accordingly the data is presented to the battery control officer for launching the missiles. After the launch, the encoded commands are transmitted from radar to guide the missile towards target. The Computer is the heart of Radar system which computes schedules and synchronizes all the system for the radar processing. It guides the missile based on the target and missile data which is then forwarded for Radar Data Encoder (RDE). RDE mainly encodes the data coming out from the computer and then converts the received data in a particular required format and then sends the converted data to Power Module. In this project, the implementation of RDE is carried on a cyclone –V-FPGA board and along the RC simulator is developed to validate the stand alone RDE unit.